멀티모달 스파이킹 뉴럴 네트워크의 성능 분석 - Han Hye Rim; Jo, Jeonghee; 박종길; Park, Seongsik (2023년도 대한전자공학회 하계학술대회 논문집, 2023)
Multimodal models have been studied as promising model that can overcome the disadvantages of the unimodal models. However, not much research has been conducted on the effectiveness of multimodality in spiking neural networks (SNNs), which have been considered a next-generation artificial neural network for their energy efficiency. Thus, in this paper, we analyzed the effectiveness through experiments on modality, model size, and noise. According to our analysis, we validated that SNNs showed greater effectiveness in multimodality than DNNs.